PENGARUH WISATAWAN MANCANEGARA TERHADAP JUMLAH HUNIAN HOTEL DI KOTA PALEMBANG MENGGUNAKAN REGRESI LINEAR - Apri Aidila Utami; Ariesta Diana Putri; Nazori Suhandi (UNIVERSITAS INDO GLOBAL MANDIRI)
The purpose of this study is to determine how much influence of foreign tourists on the number of hotel occupancy in the city of Palembang. Based on data that has been taken and tested using Linear Regression method, Respondents are taken from the number of foreign tourists coming to Palembang city (X) and the number of hotel visitors in Palembang (Y), from January to August in 2016. Meaning the influence of foreign tourists to the number of hotel occupancy in the city of Palembang is equal to 21.48%. The rest 79.62% Caused by other factors not included in the model. Y = Subject in predicted dependent variable, X = Subject to independent variable having certain value. a = Parameter intercept, b = Parameter coefficient regression independent variable. When the correlation coefficient is high, then the price of b is also great, otherwise when the negative correlation coefficient then the price b is also negative. Thus, if X = parameter (eg: 848), a = 140.4 and parameter b = 0.28 then the result is 377.4. Keywords :Linier regression, Foreign tourists, Tourism